Condomínios horizontais/loteamentos fechados e a vizinhança (in)desejada: um estudo em Uberlândia/MG - Moura, Gerusa Gonçalves (2008)
The peripherial urban landscape comes through by intense changes that requires, including, a teoretical review of the word periphery, that today can not be caracheterized anymore only by the lack of infrastructure, by the unfinished houses depending of the self-construction process, by the joint houses, by the poor and marginalized population. Currently, the periphery is also the place of residence of the elite groups that imposes to the peripherial landscape, their fortresses represented by the horizontal condominiums. They are considered as new forms of the urban habitat, that requires the (re)definition of the form and the contents of the peripherial urban. The interest in this topic made by the fact theses ventures are located in the peripherial areas and under an image of a best place of better environmental quality and, consequently, that will provide quality of life to those who inhabit there. This image is sold from the name of the condominiums and horizontal lots and of their advertisement, that value the natural areas, the security system and the glamour of living in horizontal condominiums/lots closed. In this sense, the objective of this study is to understand the surroundings of the horizontal condominiums/lots closed, from the structuring process and expanding of these building products in the cities average of the Cerrado Mineiro from the 1980s, and also the new configurations of the urban periphery, in the function of these new urban forms, having as case study, the city of Uberlândia/MG. For this, will be examined the peripherization process of the cities average and their new configuration; especially from the construction, structuring, marketing and occupation of the horizontal condominiums/lots closed, the segregation processes introduced by the same in the city of Uberlândia/MG. Also will be examined the social impacts, economic and aesthetic caused on the surrounding of these ventures, verifying that they generate or not changing, and that the same exercise some influence on the transformation of the landscape around of these fortress. The choice of surroundings of the horizontal condominiums/lots closed is justified, because the research already realized about this topic has privileged the analysis of the life inside these ventures and their own dynamic of structuring. However, little has been study in relation to impacts caused by them (horizontal condominiums/lots closed) around and, as well, how the own surrounding population asses the installation of these ventures, the benefit and damage caused, the relation between the residents inside and outside of the walls. The procedures adopted were based initially in preparation of the a theoretical skeleton consistent that serves as base in the discussions realized along of the study. Was also necessary the survey of data at the municipal administration, at the construction companies responsible for deployment of these ventures. Was realized interviews semi structured with the managers of these companies and with the residents that living around de horizontal condominiums/lots closed installed on the Southern and East Sector of the city, respecting the influence area of each. Was also realized the analysis of the advertisement and the advertising material used on the marketing of the horizontal condominiums/lots closed. The elaboration of photographic material and thematic maps was essential to the development of this study. So, the study was structured in four chapters. In the first chapter, is analysed the concept of city average, segregation, urban (re)structuring and periphery and discusses the difference between closed lots and condominiums. Also, presents itself a characterization of the horizontal condominiums/lots closed in the Latin America, and an analysis of the urban laws in relation the construction of these ventures and your link with their surroundings. In the second chapter presents itself the mapping and the general characterization of the condominiums/lots closed in the city of Uberlândia/MG and discusses the discusses the formation of the periphery from the construction of these ventures, also the new meaning of this area, from the action of the production agents of the urban space, especially, of the government and of the incorporators buildings. In the third Chapter, make an analysis of the surroundings condominiums/lots closed constructed on the Southern and East Sector of the city, the neighborhood desired and undesired, respectively, showing the influence of these ventures on the urban landscape and in the own life of the residents that lives by the side of these new urban forms. To finish, in the fourth chapter, waves a discussion about the subjective dimension and the objectives of the condominiums/lots. That methodology to analysis for a construction and evolutes that surroundings condominiums en cities.